Development of embodied listening studies with multimodal and wearable haptic interfaces for hearing accessibility in music - Cavdir, Doga (Frontiers in Computer Science, 2024)
The intersection of hearing accessibility and music research offers limited representations of the Deaf and Hard of Hearing (DHH) individuals, specifically as artists. This article presents inclusive design practices for hearing accessibility through wearable and multimodal haptic interfaces with participants with diverse hearing backgrounds. We develop a movement-based sound design practice and audio-tactile compositional vocabulary, co-created with a Deaf co-designer, to offer a more inclusive and embodied listening experience. This listening experience is evaluated with a focus group whose participants have background in music, dance, design, or accessibility in arts.By involving multiple stakeholders, we survey the participants' qualitative experiences in relation to Deaf co-designer's experience. We conclude by presenting design practices when working with movement-based musical interaction and multimodal haptics.